Perbedaan Individual (Kognitif, Bakat, Minat) Dan Implikasinya Terhadap Pembelajaran - Khairul Khalqi; Rustam; Sri Haryanti (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
Education in Indonesia, which is currently student-centered, will of course make a teacher have to be more creative and understand everything that happens to each student. With individual differences that are not limited to cognitive abilities alone, it is of course very important to examine these individual differences and their impact on the learning process. This study uses the method of literature (library research). Implications of individual differences in intelligence-based learning include impulsive/reflective style and deep/shallow style, while the implications of individual differences in talent-based learning include that it is impossible to work in the zone of proximal development, range of challenging tasks that encourage cognitive development, Students experience boredom or frustration when school assignments do not challenge and help them develop their unique abilities. The last is the implication of individual differences in interest-based learning, namely, asking for feedback from students on the learning that has been done, groups formed by the teacher taking into account students' learning interests, approaching and communicating with students in class, the teacher assists individually, the teacher involve students in the process of giving apperception, the teacher monitors student learning activities